MECHANICAL FOOD PROCESSING METHOD AND FOOD QUALITY OF LOCAL DELICACIES IN RIVERS STATE, NIGERIA - Obot, Mary Ifiok; Ndu, Eugene Chigozie, PhD (Journal Park Publishing, 2023)
Local dishes restaurant serves a major role in the provision of quick meals in a cosmopolitan area such as Port Harcourt. However, their services need to be assessed for quality to minimize the risk of contamination and poisoning. The objective of this study was to investigate the mechanical food production process on food quality of local dishes restaurants in Port Harcourt. Food production process was dimensioned with Manual Food Processing and Mechanical Food while food quality was dimensioned as Food Taste, Food Texture and Food Attractiveness. This resulted in the stating of three research questions and their corresponding null hypotheses. The descriptive survey research design was used for the study with a sample of 400 respondents drawn from Port Harcourt Metropolis. Data obtained was analyzed using Pearson Product Moment Correlation Statistics and Simple Regression Analysis for answering the research questions and testing the hypotheses. The result showed a strong positive relationship between mechanical food production process showed a moderate relationship with food taste and food texture but failed to have any significant relationship with food attractiveness. Therefore, it was recommended that irrespective of the food production process adopted by local dish restaurants, there is need to continuously consider superior food quality as strategy to satisfying their customers. Also, local dish restaurants should also prioritise chef training as this was proven to enhance food quality.